The Lack of Interest to do Counseling among Junior High School Students: Evaluation of Principals, Counselors, Teachers, and Peers Factors - Purwati, Purwati; Japar, Muhammad; Putro, Hijrah Eko (Islamic Guidance and Counseling Journal, 2020)
This study departs from the limitations of research on how principals, counselors, teachers, and peers in inhibiting students' intention to do counseling. This study aims to determine how principals, counselors, teachers, and peers influence the lack of interest in student to do counseling. 162 students from six Junior High Schools in the city of Magelang, Indonesia were involved as participants after obtaining permission from the schools. The collected data is then analyzed using correlation and path analysis to see how the relationship and influence of principals, counselors, teachers, and peers on student counseling interests, and to see how the role of peers in mediating the relationship between principals with counselors and teacher with counselors. The school principals, counselors, and teachers become serious obstacles as they being categorized in high, while peers become factors in the medium category. Principals, teachers and peers contribute positively to the lack of interest in consulting to counselors. Principal factors and teachers contribute positively to peers. Peers are mediators in the principal's relationship with the counselor and the teacher's relationship with the counselor.